'You come back fighting. That's what gives you the drive to achieve': The extraordinary psychological construction of the super-rich in entertainment documentaries. (September 2021) - Carr, Philippa; Goodman, Simon; Jowett, Adam; Abell, Jackie
Inequality in society is legitimised through the 'meritocracy myth' and existing research claims that the affluence of the super-rich is the result of their superior traits. Discursive Social Psychology examines the ways in which psychological concepts such as personality traits function in talk. This research explores how entertainment documentaries construct the traits of the super-rich to legitimise their wealth. A corpus of 41.5 hours of terrestrial UK televised broadcasts that used the term, 'super-rich' was analysed. This explored how wealthy individuals are presented as having superior psychological qualities compared to the general public in relation to their greater drive and resilience. However, wealthy individuals also talk about the development of superior traits as a response to adversity. Entertainment documentaries draw upon individualistic ideology to present wealth inequality as a natural consequence of individual differences and as a result, the current distribution of wealth is 'just' despite its negative consequences for all.